2019
DOI: 10.1002/jcp.28781
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNAs in physiological and pathological processes in asthma

Abstract: Asthma is the most common respiratory disease accompanied by lung inflammatory disorders. The main symptoms are airway obstruction, chronic inflammation due to mast cell and eosinophil activity, and the disturbance of immune responses mostly mediated by the Th2 response. Genetic background and environmental factors also contribute to the pathogenesis of asthma. Today, microRNAs (miRNAs) are known as remarkable regulators of gene expression. As a small group of noncoding singlestrand RNAs, mature miRNAs (~21 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…On the other hand, previous studies have highlighted that miR-182 may promote asthma by stimulating in ammation [39]. Our results also agree with the idea that miRs, like miR-182, miR-30 [40] and miR-221 [41], serve as potential candidates for the treatment of asthma [42]. In line with our ndings, miR-182 is also known to be signi cantly up-regulated upon Th17 differentiation [13].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, previous studies have highlighted that miR-182 may promote asthma by stimulating in ammation [39]. Our results also agree with the idea that miRs, like miR-182, miR-30 [40] and miR-221 [41], serve as potential candidates for the treatment of asthma [42]. In line with our ndings, miR-182 is also known to be signi cantly up-regulated upon Th17 differentiation [13].…”
Section: Discussionsupporting
confidence: 92%
“…Most research compares the miRNAs profile between asthmatics and controls in a variety of sample types. Other studies on miRNAs in asthma in adult population have been reported, describing a number of miRNAs such as miR-20b, miR-138, miR-143, miR-145, and others and their role in adulthood asthma ( 174 ).…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…Asthma is marked by recurrent episodes of symptoms (for example, breathlessness, cough and wheezing), airway obstruction, inflammation, and bronchial hyper-responsiveness to various forms of stimuli [58]. The role of miRNAs in asthma-related signaling pathways have been clearly explained by Mousavi et al [59] and Taka et al [60]. Nonetheless, the following are studies that emerged in recent months.…”
Section: Asthmamentioning
confidence: 99%